An examination of the gendered experiences of black women in the Black Consciousness Movement (BCM) - Rala, Tsidi (Rhodes University, 2026)
This is a qualitative MA thesis that investigates the gendered experiences and political roles of Black women in the Black Consciousness Movement (BCM). This research project sought to answer two research questions: 1) What political role did women activists play in the BCM? and 2) What is the gendered experience of women activists who participated in this Movement? To engage with these research questions, this study recruited and interviewed eight black women who were politically involved in the BCM during the apartheid era. Research participants were interviewed through semi-structured interviews. An important finding in this study is that many of the research participants were attracted to the BCM by the Movement’s philosophy which centred on black pride under slogans like “Black is Beautiful”. Participants recounted stories of personal transformation that was activated by the philosophy of the BCM. For instance, participants talked about how the BCM philosophy encouraged self-acceptance by equipping women activists with ideological tools to struggle against the white beauty standards imposed by colonialism and apartheid. However, some research participants reported that while the Movement was underpinned by a black liberation philosophy, the Movement did not prioritise women liberation. Consequently, women’s political agenda was often pushed aside. Thus, while the BCM championed racial solidarity and the psychological liberation of black people, it often marginalised and overlooked the unique struggles of black women, who faced intersecting oppressions of race, gender, and class. Ultimately, this thesis aims to contribute to the post-1994 black feminist project by making visible and documenting the experience of women activists in the BCM. This research aims to contribute to a more nuanced understanding of the BCM by foregrounding the experiences of black women and advocating for an intersectional approach to historical and political analysis. In doing so, it underscores the importance of addressing gendered inequities within liberation movements to achieve true solidarity and justice.
Keywords: Uncatalogued